Isokinetic studies for detection of functional disorders in patients with unilateral shoulder impingement syndrome - Połyniak, Katarzyna; Lisiński, Przemysław; Huber, Juliusz; Romanowski, Leszek (Journal of Medical Science, 2014)
Introduction. The isokinetic assessment allows objective evaluation of muscle strength in patients considered for surgery in cases of rotator cuff injury. Aim. The goal of this study was to define functional disorders of shoulder joint in patients with rotator cuff injury. Material and methods. The examination was conducted in two groups, ten patients each. One group consisted of subjects with rotator cuff injury while the other was a healthy control group. Isokinetic test was performed with use of Biodex System 4 Pro Device. The following parameters were evaluated: peak torque, peak torque/body weight (peak TQ/BW), total work, average power, range of movement (ROM) and peak torque ratio of external to internal rotators (ERPT/IRPT ratio). Studies of Shoulder Pain and Disability Index (SPADI) scale supplemented clinical evaluation. Results. Examination indicated a significant deficit of muscle strength during external rotation and ROM limitation only on symptomatic side in shoulder impingement group. Alteration between agonistic and antagonistic muscles strength for 2400/s was found. Significant differences between involved and uninvolved shoulders during pain and disability tests were detected. There was no correlation between result of isokinetic and SPADI tests. Conclusions. Patients after injury of rotator cuff present functional disorders that occur mainly during external rotation in isokinetic evaluation.